Comparative Assessment of Lignan Profiling and Biological Activities of Schisandra henryi Leaf and In Vitro PlantForm Bioreactor-Grown Culture Extracts - Karolina Jafernik; Paweł Kubica; Michał Dziurka; Łukasz Kulinowski; Izabela Korona-Głowniak; Hosam O. Elansary; Piotr Waligórski; Krystyna Skalicka-Woźniak; Agnieszka Szopa (MDPI AG, 2024)
This research's scope encompassed biotechnological, phytochemical, and biological studies of Schisandra henryi, including investigations into its in vitro microshoot culture grown in PlantForm bioreactors (temporary immersion systems, TISs), as well as extracts from leaves of the parent plant, focusing on anti-inflammatory, antioxidant, anticancer, and antimicrobial activities. The phytochemical analysis included the isolation and quantification of 17 compounds from dibenzocyclooctadiene, aryltetralin lignans, and neolignans using centrifugal partition chromatography (CPC), HPLC-DAD, and UHPLC-MS/MS tandem mass spectrometry with triple quadrupole mass filter methods. Higher contents of compounds were found in microshoots extracts (max. 543.99 mg/100 g DW). The major compound was schisantherin B both in the extracts from microshoots and the leaves (390.16 and 361.24 mg/100 g DW, respectively). The results of the anti-inflammatory activity in terms of the inhibition of COX-1, COX-2, sPLA2, and LOX-15 enzymes indicated that PlantForm microshoot extracts showed strong activity against COX-1 and COX-2 (for 177 mg/mL the inhibition percentage was 76% and 66%, respectively). The antioxidant potential assessed using FRAP, CUPRAC, and DPPH assays showed that extracts from microshoot cultures had 5.6, 3.8, and 3.3 times higher power compared to extracts from the leaves of the parent plant, respectively. The total polyphenol content (TPC) was 4.1 times higher in extracts from the in vitro culture compared to the leaves. The antiproliferative activity against T-cell lymphoblast line Jurkat, breast adenocarcinoma cultures (MCF-7), colon adenocarcinoma (HT-29), and cervical adenocarcinoma (HeLa), showed that both extracts have considerable effects on the tested cell lines. The antimicrobial activity tested against strains of Gram-positive and Gram-negative bacteria and fungi showed the highest activity towards H. pylori (MIC and MBC 0.625 mg/mL).